(untitled) (Medicine Today, 2014)
Anemia is the commonest hematological disorder that occurs in pregnancy. According to the recent standard laid down by WHO, anemia is present when the Hemoglobin (Hb) concentration in the peripheral blood is 11 gm/dl or less. The most common cause of anemia in pregnancy is lack of iron. Less often, it is caused by folic acid deficiency. In some populations, 80% of pregnant women are anemic. Those most at risk are women from low socio-economic groups and teenagers. Anemia is diagnosed by estimating the hemoglobin concentration and examining a peripheral blood smear for the characteristic red blood cell changes. Iron and folate supplementation is indicated during pregnancy to prevent the complications. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21314 Medicine Today 2014 Vol.26(1): 49-52